Intractable pleural effusion associated with superior vena cava and upper extremity deep vein thrombosis in a patient with advanced lung cancer. (2020) - Tsuruno, Kosuke; Tobino, Kazunori; Sakabe, Mitsukuni; Okahisa, Masanobu; Nishizawa, Saori; Yoshimine, Kohei; Ko, Yuki; Ide, Hiromi
Abstract: We herein report a case with intractable pleural effusion attributed to superior vena cava (SVC) and upper extremity deep vein thrombosis in a patient with lung cancer. A 62-year-old woman presented to our hospital with shortness of breath and bilateral upper extremity edema. One year ago, she was diagnosed with stage IVB lung adenocarcinoma with bilateral malignant pleural effusions. A genetic analysis of the cells from pleural effusion revealed an epidermal growth factor receptor (EGFR) point mutation at exon 21 (L858R); since then, she was treated with gefitinib. Although her lung cancer and metastatic lesions had markedly reduced and the tumor cells in the pleural effusion had disappeared, pleural effusion remained. Contrast-enhanced whole-body computed tomography (CT) revealed intravenous thrombosis extending from the SVC to the left brachiocephalic and subclavian veins, and her pleural effusion was attributed to this thrombosis. Anticoagulant therapy with intravenous heparin and oral warfarin was started, nevertheless, the thrombus remained and pleural effusion did not decrease. After the placement of a pleuroperitoneal shunt, her pleural effusion resolved and her symptoms improved. This case highlights the importance of awareness of SVC or upper extremity deep vein thrombosis as a differential diagnosis of intractable pleural effusion in lung cancer patients.